A Non-Doctrinal Study on the Implementation of Occupational Safety and Health (OSH) Legislation in Manufacturing Small and Medium Enterprises (SMEs) of Sabah - Sharija Che Shaari; Nik Ahmad Kamal Nik Mahmod; Farheen Baig Sardar Baig (2020)
The manufacturing industry is important to Malaysia’s GDP, nevertheless, its contribution to the statistics of occupational accidents is alarming. Many studies have shown that small and medium enterprises (SMEs) are having difficulties coping with the Occupational Safety and Health (OSH) legislation. It is important to note that the accident rate in the Malaysian manufacturing industry has been among the highest over the years. This study is therefore intended to determine if Sabah's manufacturing SMEs understand their legal obligations as required by the Factories and Machinery Act 1967 (FMA 1967), the Occupational Safety and Health Act 1994 (OSHA 1994) and related regulations. This research uses a non-doctrinal (socio-legal) approach where legal sources (statutes, case laws, legal journals) are systematically examined and the participants' input is grouped into common themes. A qualitative approach is deployed through in-depth and face-to-face interviews to gain an understanding of the viewpoints derived out of this research. The fieldwork is carried out in major towns in Sabah, namely Kota Kinabalu, Sandakan, Tawau, and Keningau. The list of participants was obtained from the Federation of Sabah Industries (FSI) and the Department of Industrial Development and Research (DIDR). It is interesting to note that many businesses are still in the darkness of their legal duties, despite acknowledging the importance of OSH legislation. It can be summarised that the smaller the businesses, the less OSH knowledge they have. The findings do not merely fill the gap in the current literature but would enable policymakers to establish better regulations or programmes that can effectively reduce the rate of accidents in manufacturing SMEs.